Molecular mechanisms of viral inhibitors of RIG-I-like receptors - Leung, Daisy W. (2012)
Activation of innate immune signaling pathways through cytosolic RIG-I like receptors (RLR) is a critical response that is antagonized by many viruses. A variety of RNA related pathogen associated molecular patterns have been identified and their role in RLR activation has been examined. Recent studies suggest that several virally encoded components that antagonize RLR signaling interact with and inhibit the interferon (IFN)-α/β activation pathway using both RNA-dependent and RNA-independent mechanisms. The structural basis for these RLR inhibitory mechanisms, as well as the multifunctional nature of viral RLR antagonists, is reviewed in the context of recent biochemical and structural studies.